A New Antifungal Agent (4-phenyl-1, 3-thiazol-2-yl) Hydrazine Induces Oxidative Damage in Candida albicans - Lv, Quan-Zhen; Ni, Ting-Jun-Hong; Li, Li-Ping; Li, Tian; Zhang, Da-Zhi; Jiang, Yuan-Ying (Frontiers in Cellular and Infection Microbiology, 2020)
A gradual rise in immunocompromised patients over past years has led to the increasing incidence of invasive fungal infections. Development of effective fungicides can not only provide new means for clinical treatment, but also reduce the occurrence of fungal resistance. We identified a new antifungal agent (4-phenyl-1, 3-thiazol-2-yl), hydrazine (numbered as 31C) which showed high-efficiency, broad-spectrum and specific activities. The minimum inhibitory concentration of 31C against pathogenic fungi was between 0.0625-4 μg/ml in vitro, while 31C had no obvious cytotoxicity to human umbilical vein endothelial cells with the concentration of 4 μg/ml. In addition, 31C of 0.5 μg/ml could exhibit significant fungicidal activity and inhibit the biofilm formation of C. albicans. In vivo fungal infection model showed that 31C of 10 mg/kg significantly increased the survival rate of Galleria mellonella. Further study revealed that 31C-treatment increased the reactive oxygen species (ROS) in C. albicans and elevated the expression of some genes related to anti-oxidative stress response, including CAP1, CTA1, TRR1, and SODs. Consistently, 31C-induced high levels of intracellular ROS resulted in considerable DNA damage, which played a critical role in antifungal-induced cellular death. The addition of ROS scavengers, such as glutathione (GSH), N-Acetyl-L-cysteine (NAC) or oligomeric proanthocyanidins (OPC), dramatically reduced the antifungal activities of 31C and rescued the 31C-induced filamentation defect. Collectively, these results showed that 31C exhibited strong antifungal activity and induced obvious oxidative damage, which indicated that compounds with a structure similar to 31C may provide new sight for antifungal drug development.